Correlation between PET/CT and CT in the staging prior to the treatment of head and neck squamous cell carcinoma - García-Curdi,Fernando (2021)
Abstract Introduction: Head and neck squamous cell carcinoma is the seventh most common malignant tumor. The advances in treatment have improved the global survival rates in the past years, although the prognosis is still grave. Objective: The aim of the present study is to evaluate the correlation between positron emission computed tomography and computed tomography at the time of staging a previously untreated head and neck squamous cell carcinoma, and to determine which of the two imaging techniques gives us more information at the time of initial diagnosis. Methods: Data from all patients diagnosed in our hospital of head and neck squamous cell carcinoma by a biopsy of any location or unknown primary tumor was collected, between January 2012 and July 2017. In all cases, computed tomography and positron emission computed tomography were performed with a maximum of 30 days difference between them and patients had not received any prior treatment to staging. The stage given to each case was compared based solely on the physical examination, only on the computed tomography/positron emission computed tomography, with respect to the stage given by the tumor board, observing the concordance obtained through Cramer's V statistical test. Results: We performed a comparative analysis obtaining a correlation of 0.729 between the stage given by the tumor board and the one assigned based on the physical examination without imaging techniques. When only using computed tomography as an imaging method, the correlation was 0.848, whereas with only the use of positron emission computed tomography it was estimated at 0.957. When comparing the statistical association between staging using exclusively one of the two imaging techniques, correlation was 0.855. Conclusion: Positron emission computed tomography is useful for the diagnosis of head and neck squamous cell carcinoma, improving the patient's staging especially when detecting cervical and distant metastases. Therefore, we consider that the use of positron emission computed tomography for the staging of patients with head and neck squamous cell carcinoma is a diagnostic test to be considered.